2021
DOI: 10.3390/toxins13050298
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Food Endotoxin on Infant Health

Abstract: Endotoxin is a complex molecule derived from the outer membrane of Gram-negative bacteria, and it has strong thermal stability. The processing of infant food can kill pathogenic bacteria but cannot remove endotoxin. Because the intestinal structure of infants is not fully developed, residual endotoxin poses a threat to their health by damaging the intestinal flora and inducing intestinal inflammation, obesity, and sepsis, among others. This paper discusses the sources and contents of endotoxin in infant food a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 143 publications
0
15
0
Order By: Relevance
“…There is some evidence that low amounts of endotoxin may be bene cial for both the host and its microbiome. (Wu et al, 2021) Animal studies have shown that low endotoxin amounts may have a probiotic effect, reduce allergic diseases, and aid immune development. (Inagawa et al, 2011;Smit et al, 2009;Taniguchi et al, 2009;Wassenaar and Zimmermann, 2018) Further study of this area is needed as safe amounts of endotoxin may depend on gut health and host immunity.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There is some evidence that low amounts of endotoxin may be bene cial for both the host and its microbiome. (Wu et al, 2021) Animal studies have shown that low endotoxin amounts may have a probiotic effect, reduce allergic diseases, and aid immune development. (Inagawa et al, 2011;Smit et al, 2009;Taniguchi et al, 2009;Wassenaar and Zimmermann, 2018) Further study of this area is needed as safe amounts of endotoxin may depend on gut health and host immunity.…”
Section: Resultsmentioning
confidence: 99%
“…Several factors in the collection, management and production of milk and milk-derived products can affect endotoxin content. (Wu et al, 2021) While pasteurization eliminates bacteria, if there are large amounts of Gram-negative bacteria present at the time of pasteurization, high amounts of endotoxin will be released into the milk. After milk collection, milk can be stored in milk tanks and then transported at temperatures in which some Gram-negative bacteria (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations